The Organizational Transformation of Twitter into X Following the Acquisition and Leadership Transition - Dinda Tiara Luqman; Yunizar Yunizar; Wa Ode Zusnita Mizu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Organizations often undergo changes driven by various internal challenges, such as shifts in ownership that include mergers, acquisitions, and privatization. These changes have significant impacts on organizational structure, culture, and business strategy. Twitter, which was founded in 2007 in California with Jack Dorsey as CEO, experienced a major transformation when X Holdings acquired the company in April 2023. Following this acquisition, the organizational structure and leadership changed significantly. In addition to changes in corporate structure and strategy, the CEO position also shifted with the appointment of new executives and leaders. The purpose of this study is to explain the most significant changes that occurred at Twitter. These changes include transformations in management and ownership, policies and terms of use, new products and services, technological innovation, work culture, and internal policies.